2015
DOI: 10.1093/femsec/fiv149
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and genomic analysis ofMethanomassiliicoccalesin wetlands and animal intestinal tracts reveals clade-specific habitat preferences

Abstract: Methanogenic Thermoplasmata of the novel order Methanomassiliicoccales were recently discovered in human and animal gastro-intestinal tracts (GITs). However, their distribution in other methanogenic environments has not been addressed systematically. Here, we surveyed Methanomassiliicoccales presence in wetland soils, a globally important source of methane emissions to the atmosphere, and in the GITs of different animals by PCR targeting their 16S rRNA and methyl:coenzyme M reductase (α-subunit) genes. We dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
120
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(136 citation statements)
references
References 70 publications
14
120
2
Order By: Relevance
“…This supports recent metagenomic studies, which showed that besides gut and rumen environments (6,13,14), Methanomassiliicoccales also occur ubiquitously in marine and terrestrial anaerobic environments (10,15,82,83). Similarly to the case for WOR, 16S rRNA gene sequences of Methanomassiliicoccales were not reported for the investigated sites, likely due to a mismatch of commonly used primers against hitherto-undetected clades (22), while other uncultured Thermoplasmata were detected (84).…”
Section: Lipid Inventory Of M Luminyensis Compared To Other Archaeasupporting
confidence: 87%
See 2 more Smart Citations
“…This supports recent metagenomic studies, which showed that besides gut and rumen environments (6,13,14), Methanomassiliicoccales also occur ubiquitously in marine and terrestrial anaerobic environments (10,15,82,83). Similarly to the case for WOR, 16S rRNA gene sequences of Methanomassiliicoccales were not reported for the investigated sites, likely due to a mismatch of commonly used primers against hitherto-undetected clades (22), while other uncultured Thermoplasmata were detected (84).…”
Section: Lipid Inventory Of M Luminyensis Compared To Other Archaeasupporting
confidence: 87%
“…1). In fact, members of the "environmental clade" of Methanomassiliicoccales were previously assigned to TMEG (15). Although Methanomassiliicoccales were not specifically described in WOR sediments, which is likely due to the low coverage of commonly used primers for Methanomassiliicoccales, closely related clades such as MBG-D and TMEG were abundant in these samples (35,80).…”
Section: Lipid Inventory Of M Luminyensis Compared To Other Archaeamentioning
confidence: 95%
See 1 more Smart Citation
“…In the meantime, we identified two archaeal taxa, Methanomassiliicoccales and Methanobrevibacter ruminantium, as the most active methanogens in the rumen of steers fed a barley diet. Methanomassiliicoccales utilize methanol and methylamines as major energy and carbon sources to produce methane (19,36), while Methanobrevibacter ruminantium produces CH 4 by utilizing CO 2 , formate, and H 2 as substrates (3,37). Their high abundances suggest that the methyl compound conversion route and the CO 2 reduction route are the major methanogenesis pathways in the rumen of beef steers fed a barley-based diet.…”
Section: Discussionmentioning
confidence: 99%
“…In rumen, the aceticlastic pathway was not important with low numbers of Methanosarcina retrieved [13,14]. Recent years, methylotrophic Methanomassiliicocales, which was one of the most important methanogens populations [15,16], was found to be abundant in some rumens [17].…”
Section: Introductionmentioning
confidence: 99%